Shear strength improvement of foundation soil by using polymer fiber reinforcement - Lee, Kok Wai (2012)
One major problem related to construction on foundation soil is the low shear strength of soil. However previous researcher have shown that The shear strength could increase significantly upon consolidation and hence some improvement methods have been developed to increase the bearing capacity of the foundation soil. The purpose of this project is to evaluate the increase of shear strength of fiber reinforced sand. For this study, the samples were prepared under several consolidation pressures: 136.2kPa, 272.5kPa and 408.8kPa. The shear strength of samples are obtain by conducting the triaxial test which also known as shear box test. The results proved that there is an increase in shear strength due to the fiber reinforcement. The initial value of shear strength developed from the results of Triaxial testing was found to be increase after reinforced with the fiber, however the ratio of strength increase is 0.08 which is lower as compared to published data.